A pesquisa de clima organizacional e o neoliberalismo: alguns apontamentos - Estácio, Yone de Paula Massmann (Universidade Federal de São Carlos, 2023)
The organizational climate survey is a tool (a technique) with the purpose of diagnosing the possible challenges of a business organization promoting improvements in quality, productivity and internal policies. It is a tool used in the field of management by companies. The work was developed through a systematic literature review. In this article, the objective was to position this technical instrument of organizational climate research in the field of critical research. Based on the assumption that we are living in the neoliberal moment of capitalism, we seek to analyze whether there is a relationship between the creation and practice of the organizational climate tool and neoliberalism
Organizational climate research and neoliberalism: some notes
Keywords: Neoliberalismo; Sujeito empresarial; Clima organizacional; Neoliberalism; Business subject; Organizational climate; CIENCIAS HUMANAS::SOCIOLOGIA